2020
DOI: 10.1088/1742-6596/1687/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of section properties on thin walled beam sections with restrained torsion

Abstract: In this paper the influence of section properties on thin walled beam sections with restrained torsion is studied by considering the angle of twisting for non-uniform torsion. The study is based on the governing equation for non-uniform torsion of thin-walled beam of open and closed cross-sections, including the restrained behavior. The hyperbolic shape functions is used to generate the general solution for homogenous equation as it gives the exact results in accordance with the analytical solution. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Numerical and experimental investigations of thin-walled structures subjected to bending and torsion revealed that it is dependent on section properties and that non-uniform torsion is influenced by moments [13]. Various studies use section properties as a primary criterion for analyzing finite element methods of thin-walled sections with restrained torsion [14][15][16][17][18][19]. Typically, section properties were used as a benchmark for predicting the behavior of open and closed thin-walled sections in those studies [20].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical and experimental investigations of thin-walled structures subjected to bending and torsion revealed that it is dependent on section properties and that non-uniform torsion is influenced by moments [13]. Various studies use section properties as a primary criterion for analyzing finite element methods of thin-walled sections with restrained torsion [14][15][16][17][18][19]. Typically, section properties were used as a benchmark for predicting the behavior of open and closed thin-walled sections in those studies [20].…”
Section: Introductionmentioning
confidence: 99%